Educação a Distância Online e Formação de Professores: Práticas de pesquisas em Educação Matemática no estado de São Paulo - Paulin, Juliana França Viol [UNESP]; Miskulin, Rosana Giaretta Sguerra [UNESP] (FapUNIFESP (SciELO), 2015)
This paper presents a mapping on Mathematics Education Theses and Dissertations dealing with Teacher Education and Distance Learning. Thus, we are guided according to the qualitative perspective of meta-analysis, and the data were analyzed following procedures, which are based on some concepts of Content Analysis. This critical mapping of Theses and Dissertations revealed six themes representing the research trends on the subject investigated: didactic and pedagogical aspects of distance learning; Epistemological aspects of distance learning; Public Policy for Online Teacher Education; Practice teacher Lecturer in the context of Online learning; Formative processes of mathematics teachers in the context of Online learning and Process implementation of Online Teacher Education courses. We emphasize that the analysis of the data revealed that the research practices in mathematics education about the Teacher Education and Online learning is subject to the process of evolution and propagation of Information and Communication Technologies (ICT) in society and consequently in Education. Furthermore, it was possible to identify particular features of the formation processes in online contexts that reveal the potential of Online learning for Teacher Education.
Distance learning and teachers education: Research practices in mathematics education in São Paulo state
Keywords: Mapping; Mathematics Education; Mathematics Teacher Education; Metaanalysis; Online Learning